Implementation of QRIS Digital Payments to Encourage The Development of Local MSMEs in Bali - Permana, Dewa Gde Yoga; Aryowiloto, Julang (Yayasan Ilomata, 2024)
The presence of QRIS can be applied at various business scales, including MSMEs which are an important pillar of the Indonesian economy. The problem in this research is to determine the implementation of using QRIS as a payment method in the growth of MSMEs in Bali? This research aims to see the level of development of local MSMEs in Bali with QRIS as their digital payment. This research is quantitative descriptive. By using this method, the data collected only follows the criteria and objectives of this research for MSMEs that use the QRIS digital payment system. The results of this research analysis show that the growth of MSME data for each district in Bali has increased, as proven from the beginning of 2020 to August 2023. Seeing the increase in the number of QRIS merchants every year in the Bali Province region illustrates the positive impact it has had on the use of QRIS as a digital payment system. By using a digital-based payment system (QRIS), their merchandise turnover has increased rapidly, thereby improving the economic development of local Balinese MSMEs. Many customers are switching from cash payments to transactions using the QRIS digital payment medium, because of its convenience and security. So more and more local Balinese MSMEs are using QRIS, indicating that QRIS is improving the economy of MSMEs in Bali.